HOW ACCURATE GOOGLE TRANSLATE IN TRANSLATING JAVANESE HUMOUR “MBAH MINTO VS BOCIL” INTO ENGLISH VERSION - Ika Oktaria Cahyaningrum; Didit Kurniadi; Budi Purnomo (PT Akselerasi Karya Mandiri, 2023)
Google translate as a translation machine provides various conveniences for its users, approximately 109 languages are provided on google translate. The latest update of this application is the Java language. In this study, the researcher took the research object for the data from Javanese humor entitled